The Determinant Factors of Real Estate Investment Trust (REIT)’s Performance: Evidence from Asian REITs - Mohamad, Nor Edi Azhar Binti; Zolkifli, Ilyas Ariefin Bin (UI Scholars Hub, 2014)
This paper investigates the factors that can influence the Real Estate Investment Trust (REIT)’s performance, paying particular attention to the listed REIT’s in Asian. Samples of 45 Asian listed REITs are selected from five different countries namely Taiwan, Thailand, Malaysia, Hong Kong, Japan and Singapore for 5 years basis from 2007 to 2011 with 225 observations. Study used Net Asset value (NAV) and Return as the proxy for REITs performance while risk, dividend yield, net income and size to represent the determinants variable. Applying correlations and multiple regression analysis, the results provide evidence on the association between NAV and return with risk, dividend yield, net income and size of REITs. Results of this study are hoped to help the investors and portfolio managers to deepen their understanding of the dependence factors that might influence the performance of REITs in Asian.